Unified power quality conditioner supplied by fuel cell system via SEPIC converter - Benadid Slimane; Abdelkhalek Othmane; Abdallah Ben Abdelkader (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper presents a combined operation of the Unified Power Quality Conditioner (UPQC) with Fuel cell system (FC). The proposed system consists of a series inverter, a shunt inverter and a Fuel cell that is connected with the DC link of UPQC through a back boost converter, where it is a SEPIC converter. The mean purpose for using the SEPIC converter is ensuring a constant DC link voltage value and to make the FC system intervening only in the case when the DC link energy is insufficient. Excepting this case, the FC system will be in the standby state. To validate the proposed topology, several sags of source voltage have been applied, at the point of common coupling (PCC).The simulation results from MATLAB/SIMULINK are discussed to verify the proposed topology.